JOURNALISM: THE THIRD HABITAT - Sidorov, Viktor; Kurushkin, Sergey (Revista Inclusiones, 2020)
The relevance of the article is predetermined by qualitative shifts in the information environment of society, where social and technological changes in its functioning had decisive influence on the emergence of a new, network journalistic habitat – the third one –after the newspaper and magazine habitat and the broadcast (radio and television) habitat. The real-time feedback to the journalist from the audience was the decisive and ongoing factor in the emergence of the third habitat. The idea of the relevant problem has predetermined the study of the past scientific works on the theory of journalism by Russian and foreign scientists (B. Misonzhnikov, E. Prokhorov, S. Korkonosenko, V. Egorov, G. Maletzke, and others). The issues of the journalism functioning have been studied in relation to the newspaper and magazine habitat and to the broadcast habitat in their works. Much attention has been paid to the modern research on the topic by M. Castells, D. McQuail, and J. Keane about the connection between the transformations of society in general and its media space.